Cdk7 Is Required for Activity-Dependent Neuronal Gene Expression, Long-Lasting Synaptic Plasticity and Long-Term Memory - He, Guiqin; Yang, Xiangyu; Wang, Guo; Qi, Junxia; Mao, Rui; Wu, Zhengping; Zhou, Zikai (Frontiers in Molecular Neuroscience, 2017)
In the brain, de novo gene expression driven by learning-associated neuronal activities is critical for the formation of long-term memories. However, the signaling machinery mediating neuronal activity-induced gene expression, especially the rapid transcription of immediate-early genes (IEGs) remains unclear. Cyclin-dependent kinases (Cdks) are a family of serine/threonine kinases that have been firmly established as key regulators of transcription processes underling coordinated cell cycle entry and sequential progression in nearly all types of proliferative cells. Cdk7 is a subunit of transcriptional initiation factor II-H (TFIIH) and the only known Cdk-activating kinase (CAK) in metazoans. Recent studies using a novel Cdk7 specific covalent inhibitor, THZ1, revealed important roles of Cdk7 in transcription regulation in cancer cells. However, whether Cdk7 plays a role in the regulation of transcription in neurons remains unknown. In this study, we present evidence demonstrating that, in post-mitotic neurons, Cdk7 activity is positively correlated with neuronal activities in cultured primary neurons, acute hippocampal slices and in the brain. Cdk7 inhibition by THZ1 significantly suppressed mRNA levels of IEGs, selectively impaired transcription-dependent late-phase long-term potentiation (L-LTP) and prevented the formation of long-term memories.